Analisis Efektivitas Operasional Layanan Les Privat Berbasis Overall Equipment Effectiveness (OEE): Studi Kasus pada Usaha Pendidikan Nonformal - Mutiara Fitridiani; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2026)
This study examines the operational effectiveness of private tutoring services by adapting the Overall Equipment Effectiveness (OEE) concept to the non-formal education sector. Using a descriptive qualitative approach based on a case study, data was collected through observations, schedule documentation, and evaluation records over an operational period. The analysis revealed Availability of 90%, Performance of 89%, and Quality of 90%, resulting in an OEE of 72%. This figure indicates that service effectiveness is quite good but has not yet reached world-class levels (generally around 85% or higher) as recommended by OEE literature adapted for the service and education sectors. The novelty of this study lies in the use of OEE as a data-driven measurement tool in the context of non-formal education services, specifically private tutoring, to encourage evidence-based continuous improvement. The implications of this study provide an evaluative framework and practical recommendations for private tutoring program managers to enhance service quality through systematic and measurable improvements.